First molecular detection of Sarcocystis suihominis in a domestic pig of Nigeria - Obadiah, Happiness Igwe; Wieser, Sara Nathaly; Nzelu, Ifeoma Nancy; Olaolu, Olushola Samuel; Jagab, Hafsat Shaiabu; Obishakin, Emmanuel Tumininu; Omudu, Edward Agbo; Atu, Bernard Ortwer; Byanet, Obadiah; Schnittger, Leonhard; Florin-Christensen, Monica (Springer, 2024)
Sarcocystis are Apicomplexan protozoa with a dixenous life cycle that includes a predator and a prey as definitive and intermediate hosts, respectively. Domestic and wild pigs are intermediate hosts of S. suihominis, with formation of sarcocysts in their muscles, while humans and non-human primates act as final hosts. After ingesting raw or undercooked sarcocyst-infested pork, signs of gastroenteritis including inappetence, nausea, vomiting, and diarrhea may develop in humans. Moreover, excretion of infective forms with human feces leads to dissemination of the parasite in the environment. In this study, macroscopic sarcocysts of white color, oval shape, and a diameter of approximately 3–8 mm were found in the skeletal muscle of a slaughtered domestic pig (Sus scrofa domesticus) destined for human consumption in an abattoir of Makurdi, Benue State, Nigeria. Sarcocyst DNA was used as template to PCR amplify the near-complete length of the 18S rRNA gene and a fragment of the cytochrome c oxidase subunit 1 (cox-1) gene. Amplicons were sequenced and used to construct phylogenetic trees with selected available Sarcocystis spp. sequences. In both cases, the placement of the analyzed sequences with S. suihominis was strongly supported, confirming the species identity of this macroscopic sarcocyst-forming parasite. This constitutes the first molecular identification of S. suihominis in Nigeria and the African continent. Proximity between pigs and humans, and poor sanitary conditions frequently encountered in pig farms of Nigeria might favor the dissemination of this zoonotic parasite, posing a threat to public health.